Disaster Management and Identification of Safe and Hazardous Landslide Zones in Rural Areas of Sarwabad County - vahid riahi (تحقیقات کاربردی علوم جغرافیایی, 2015)
Iran's rural settlements, in spite of their comprehensive and multi-faceted developments in the last decades, are still considered to be among the settlements faced with crucial challenges in the face of environmental hazards. As a result, prearrangement for upcoming events and disasters, as well as paying attention to the management of rural disaster in dealing with particularly natural events turn out to be necessary. The rural areas of Sarwabad, in Kurdistan, are also considered among the areas susceptible to natural disasters, such as floods, earthquakes, and landslides. The purpose of the research is the identification of settlements, and safe and hazardous landslide zones with particular focus on disaster management in Sarwabad. This research is methodologically analytical and essentially functional, and, by using geographical information system (GIS) and the analytical hierarchical process (AHP), the researchers analyzed the data and the layers and provided the ultimate version of combined hazard maps and also overlaying maps for the purpose of factorial assessment. The findings have been in the form of spatio-populatory analysis of the settlements, and resulted in identifying the safe and unsafe villages and zones. Moreover, it is found that nearly 46 percent of the rural population and 31 villages of the area are located in safe or low-hazard-level landslides, while the rest of the settlements and rural population are located in the mid and high-hazard-level zones and, as such, are need to be secured in these zones.